Producción organica de banano orito (musa acuminata AA) y su incidencia en el nivel de comercialización asociativo en el cantón la Mana. Provincia del Cotopaxi. Año 2014 - Cañas Trejo, Shirley María (2015)
The draft Organic Banana Production Orito (Musa acuminata AA) and its impact on the level of Associative marketing in Canton La Mana. Seeks to demonstrate that Ecuador is an agricultural country and enjoys exceptional climatic conditions, which together with the riches of the soil allow harvest quality products. Banana production (orito) in the country is increasing, it has grown from a growing domestic predominant use to become an important commercial crop especially for small farmers who now sell their products in domestic market or for export, that contribute economic development of the country. The nine POs Canton La Mana, recorded an annual output of 1'640.967 orito organic banana boxes, with an average price of $ 3.5 box, which amount to $ 5'743.384,50. Banana exports (orito) satisfy different markets like Russia, Ukraine, Germany, China etc. where the economy is one of the most stable in the world, and the market remains a tendency to consumption of exotic fruits.